ANALISIS ROYALTI HAK CIPTA LAGU SEBAGAI HARTA BERSAMA DALAM GUGATAN CERAI - Indriyani Anhar, Hanifah (LPPM Universitas Bina Bangsa, 2024)
Disputes between humans are common thing. Likewhise in carrying out domestic life. Moreover, there are many problems between husband and wife. Not infrequently, in the end, divorce remains an option. If a divorce occurs, various other problems will arise. Problems that can arise as a result of divorce include child custody issues if the result of the marriage has been blessed with children or issues of shared assets (joint assets). Problems regarding the division of joint assets are now increasingly growing. One of them concerns Intellectual Property Rights such as song copyright royalties. Are song copyright royalties as a joint asset? How is it divided in a divorce?